Map of part of Manitoba and North West Territory showing subdivided into townships that portion in which the Hudson's Bay Co . - Aldous, Montague (Surveyor); Burland Lithographic Company (Lithographer)
This is a map of land distribution in Manitoba and the Northwest Territories at the end of 19th century. It consists of two parts: part 1 - general map of the region showing inspected lands and Hudson's Bay Company's and Indian reserves; and part 2 - Hudson's Bay Company's information on cities, farming, lands, climate, municipal organization, schools, timber and fuel industries, transportation and communication in Manitoba and the Northwest Territories [see also record for part 2]. Shows inspected lands, Hudson's Bay Company's reserved lands, Indian reserves, railways, citties and towns. Scale approximately 1:1,770,000. Relief shown by hachures. Material digitized as part of an Academic Innovation Fund (AIF), awarded in 2018. For more information see: http://avptl.info.yorku.ca/academic-innovation-fund/ .